2022
DOI: 10.3389/fmicb.2021.781746
|View full text |Cite
|
Sign up to set email alerts
|

The Pass-on Effect of Tetracycline-Induced Honey Bee (Apis mellifera) Gut Community Dysbiosis

Abstract: Gut microbial community plays an important role in the regulation of insect health. Antibiotic treatment is powerful to fight bacterial infections, while it also causes collateral damage to gut microbiome, which may have long-lasting consequences for host health. However, current studies on honey bees mainly focus on the impact of direct exposure to antibiotics on individual bees, and little is known about the impact of social transmission of antibiotic-induced gut community disorder in honey bee colonies. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…Antibiotic exposure causes dysbiosis, with effects on host health ( Francino, 2016 ; Neuman et al, 2018 ), the resistome (genes involved in resistance responses), and gut bacterial diversity ( Li et al, 2019 ; Xu et al, 2020 ). We found that short-term dysbiosis could be transferred to subsequent worker bee generations which is in line with previous experiments in honey bees and flies ( Ourry et al, 2020 ; Jia et al, 2022 ). In our experiment, tetracycline disrupted the normally stable bee gut community, which did not recover over subsequent generations even after antibiotic administration was ceased.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Antibiotic exposure causes dysbiosis, with effects on host health ( Francino, 2016 ; Neuman et al, 2018 ), the resistome (genes involved in resistance responses), and gut bacterial diversity ( Li et al, 2019 ; Xu et al, 2020 ). We found that short-term dysbiosis could be transferred to subsequent worker bee generations which is in line with previous experiments in honey bees and flies ( Ourry et al, 2020 ; Jia et al, 2022 ). In our experiment, tetracycline disrupted the normally stable bee gut community, which did not recover over subsequent generations even after antibiotic administration was ceased.…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the direct action of antibiotics on bacteria, we observed substantial changes in the honey bee gut community after tetracycline exposure. While in previous studies, antibiotics were shown to affect the honey bee microbiome ( Powell et al, 2021 ; Tian et al, 2012 ; Moullan et al, 2015 ; Li et al, 2017 ; Raymann et al, 2017 ; Baffoni et al, 2021 ; Jia et al, 2022 ), it rarely led to the total collapse of bacterial species as we observed in our design. At the end of the first cycle, four bacterial genera disappeared from guts of antibiotic-fed bees ( Figure 5 and Supplementary Figure S9 ).…”
Section: Discussioncontrasting
confidence: 44%
See 2 more Smart Citations
“…Moreover, long-lasting treatments and their common use in prophylaxis, as well as failing to eliminate bacterial spores, may cause or accelerate mechanisms of antibiotic resistance [ 25 , 26 , 27 , 28 ]. Additionally, antibiotics may leave residues in hive products [ 29 , 30 , 31 ] and also cause honey bee gut community dysbiosis [ 32 , 33 , 34 ]. On this matter, a growing number of research studies have revealed the relationship between disease states and variation in the native microbiome of honey bees, suggesting that the integrity of the microbiome correlates with disease susceptibility and, on a more general level, with the health status of honey bees [ 11 , 31 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%